Optical member and method for manufacturing optical member
By designing an optical member including a polarizer, a transparent plate, a phase difference layer and an adhesive layer in an organic EL panel, the problems of discoloration, decolorization and insufficient durability of the polarizer are solved, and higher durability and stability.
Patent Information
- Application Number
- CN202411036611.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-01
- Filing Date
- 2024-07-31
- Publication Date
- 2025-02-14
AI Technical Summary
The polarizer in the organic EL panel is prone to discoloration and decolorization, and has insufficient durability, especially when the transparent plate is arranged to protect the display.
An optical member is designed, including a polarizer, a transparent plate, a phase difference layer and a first adhesive layer, the polarizer has a polarizer and a first protective layer on the first and second main surfaces, and the transparent plate is arranged at The first main surface side of the polarizer, the phase difference layer is arranged on the second main surface side of the polarizer, the first adhesive layer is located between the polarizer and the phase difference layer, and the moisture content thereof is controlled to be 3g/m2. the following.
It effectively suppresses discoloration and decolorization of the polarizer, and significantly improves its durability, so that the optical components can maintain stable performance under high temperature environments.
Smart Images

Figure CN119439346A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an optical component and a method for producing the optical component. Background Art
[0002] In recent years, with the popularity of thin displays, displays (organic EL display devices) equipped with organic electroluminescent (EL) panels have been proposed. Organic EL panels are prone to problems such as external light reflection and background reflection due to their highly reflective metal layers. Therefore, it is known that a polarizer with a phase difference layer formed by combining a polarizer and a phase difference plate is provided on the visible side of the organic EL panel body to prevent these problems (e.g., Patent Documents 1 and 2).
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2002-372622
[0006] Patent Document 2: Japanese Patent No. 3325560 Summary of the invention
[0007] Problems to be solved by the invention
[0008] With the popularization of thin displays, sometimes extremely high durability is required for organic EL panels, and sometimes extremely high durability is also required for polarizers. However, the polarizers provided in organic EL display devices tend to be easily discolored and faded. This tendency is significant when a transparent plate is provided on the visible side for the purpose of protecting the display.
[0009] The present invention has been made to solve the above-mentioned problems, and a main object of the present invention is to provide an optical member which suppresses discoloration and fading of a polarizing plate and has excellent durability.
[0010] Means for solving problems
[0011] 1. An optical member according to an embodiment of the present invention comprises: a polarizing plate, the polarizing plate comprising a polarizer having a first principal surface and a second principal surface facing each other, and a first protective layer disposed on the first principal surface side of the polarizer; a transparent plate disposed on the first principal surface side of the polarizer; a phase difference layer disposed on the second principal surface side of the polarizer; and a first adhesive layer disposed between the polarizing plate and the phase difference layer and disposed adjacent to the polarizing plate, wherein the moisture content of the laminated portion of the polarizing plate and the first adhesive layer is 3 g / m 2 the following.
[0012] 2. An organic EL panel according to an embodiment of the present invention includes the optical member described in 1 above and an organic EL panel body.
[0013] 3. A method for manufacturing an optical member according to an embodiment of the present invention comprises: preparing a laminated body, the laminated body comprising a polarizer and a first adhesive layer, the polarizer comprising a polarizer having a first principal surface and a second principal surface facing each other and a first protective layer disposed on the first principal surface side of the polarizer, the first adhesive layer being disposed on the second principal surface side of the polarizer and adjacent to the polarizer, the moisture content of a laminated portion of the polarizer and the first adhesive layer being 3 g / m 2 Next, a transparent plate is provided on the polarizing plate side of the laminate; and a retardation layer is bonded to the first adhesive layer of the laminate.
[0014] 4. A method for manufacturing an optical member according to another embodiment of the present invention comprises: preparing a laminated body, the laminated body comprising a polarizing plate, a first adhesive layer arranged adjacent to the polarizing plate, and a phase difference layer arranged on the second principal surface side of the polarizer in this order; the polarizing plate comprises a polarizer having a first principal surface and a second principal surface facing each other, and a first protective layer arranged on the first principal surface side of the polarizer; the moisture content of the laminated portion of the polarizing plate and the first adhesive layer is 3 g / m 2 Next, a transparent plate is provided on the polarizing plate side of the laminate.
[0015] Effects of the Invention
[0016] According to the embodiment of the present invention, it is possible to provide an optical member in which discoloration and fading of a polarizing plate are suppressed and which has excellent durability. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a schematic cross-sectional view showing a schematic structure of an optical member according to one embodiment of the present invention.
[0018] Figure 2 This is a schematic cross-sectional view schematically showing an organic EL panel according to one embodiment of the present invention.
[0019] Figure 3A This is a photograph of the optical member of Comparative Example 1 observed from above before heating.
[0020] Figure 3B This is a photograph of the optical member of Comparative Example 1 observed from above after heating.
[0021] Explanation of symbols
[0022] 10 Polarizer
[0023] 21 First protective layer
[0024] 22 Second protective layer
[0025] 30 Polarizer
[0026] 40 Phase difference layer
[0027] 51 first adhesive layer
[0028] 52 second adhesive layer
[0029] 53 third adhesive layer
[0030] 60 Transparent Plate
[0031] 70 Organic EL panel body
[0032] 100 optical components
[0033] 200 organic EL panel DETAILED DESCRIPTION
[0034] Hereinafter, the embodiments of the present invention will be described with reference to the accompanying drawings, but the present invention is not limited to these embodiments. In order to make the description clearer, the drawings sometimes schematically show the width, thickness, shape, etc. of each part compared with the embodiments, but this is an example and does not limit the interpretation of the present invention. In addition, for the drawings, the same or equivalent elements are marked with the same symbols, and repeated descriptions are sometimes omitted.
[0035] (Definition of Terms and Symbols)
[0036] The definitions of terms and symbols in this specification are as follows.
[0037] (1) Refractive index (nx, ny, nz)
[0038] “nx” is the refractive index in the direction where the refractive index in the plane is maximum (ie, the slow axis direction), “ny” is the refractive index in the direction orthogonal to the slow axis in the plane (ie, the fast axis direction), and “nz” is the refractive index in the thickness direction.
[0039] (2) In-plane phase difference (Re)
[0040] "Re(λ)" is the in-plane phase difference measured by light of wavelength λnm at 23°C. For example, "Re(550)" is the in-plane phase difference measured by light of wavelength 550nm at 23°C. When the thickness of the layer (film) is set to d(nm), Re(λ) is calculated by the formula: Re(λ) = (nx-ny)×d.
[0041] (3) Retardation in the thickness direction (Rth)
[0042] "Rth(λ)" is the phase difference in the thickness direction measured by light of wavelength λnm at 23°C. For example, "Rth(550)" is the phase difference in the thickness direction measured by light of wavelength 550nm at 23°C. When the thickness of the layer (film) is set to d(nm), Rth(λ) is calculated by the formula: Rth(λ) = (nx-nz)×d.
[0043] (4) Nz coefficient
[0044] The Nz coefficient is obtained by Nz=Rth / Re.
[0045] (5) Angle
[0046] When an angle is mentioned in this specification, the angle includes both clockwise and counterclockwise relative to a reference direction. Therefore, for example, "45°" means ±45°.
[0047] [Optical components]
[0048] Figure 1 This is a schematic cross-sectional view showing a schematic structure of an optical member according to one embodiment of the present invention.
[0049] The optical component 100 includes a polarizer 30. The polarizer 30 includes a polarizer 10 having a first principal surface 10a and a second principal surface 10b opposite to each other, a first protective layer 21 arranged on the first principal surface 10a side of the polarizer 10, and a second protective layer 22 arranged on the second principal surface 10b side of the polarizer 10. In addition, the optical component 100 includes a phase difference layer 40 arranged on the second principal surface 10b side of the polarizer 10 and a first adhesive layer 51 arranged between the polarizer 30 and the phase difference layer 40. Different from the illustrated example, the second protective layer 22 may also be omitted. In this case, the phase difference layer 40 may also function as a protective layer of the polarizer 10. The first adhesive layer 51 is arranged adjacent to the polarizer 30. Specifically, the first adhesive layer 51 is arranged adjacent to the second protective layer 22 or the polarizer 10.
[0050] Although not shown, the polarizing plate 30 may include an adhesive layer for bonding the protective layer to the polarizer 10. Figure 1 In the polarizing plate 30 shown in , an adhesive layer may be provided between the polarizer 10 and the first protective layer 21 , and an adhesive layer may be provided between the polarizer 10 and the second protective layer 22 .
[0051] The phase difference layer 40 shown in the figure is a single layer, but unlike the example shown in the figure, the phase difference layer 40 may also have a stacked structure of two or more layers. For example, the phase difference layer 40 may also include two or more layers with different optical characteristics such as refractive index characteristics, in-plane phase difference, Nz coefficient, photoelastic coefficient, etc.
[0052] The optical member 100 includes a transparent plate 60 disposed on the first principal surface 10a side of the polarizer 10. The transparent plate 60 is bonded to the polarizer 30 via the second adhesive layer 52. The optical member 100 is typically mounted on an organic EL panel. In the organic EL panel, the optical member 100 can be arranged so that the transparent plate 60 is located on the visible side compared to the polarizer 30.
[0053] A third adhesive layer 53 is provided on the surface of the phase difference layer 40. Through the third adhesive layer 53, for example, the optical component 100 is made to be attached to the main body of the organic EL panel. Although not shown in the figure, a release liner can be attached to the surface of the third adhesive layer 53 in actual use, and the third adhesive layer 53 is protected by the release liner. The release liner is, for example, temporarily attached to the third adhesive layer 53 until the optical component 100 is provided for use. Specifically, the release liner is temporarily attached to the third adhesive layer 53 until the optical component 100 is mounted on the organic EL panel. As the release liner, a plastic film whose surface is coated with a release agent is typically used.
[0054] In the optical member 100 , the water content of the laminated portion of the polarizing plate 30 and the first adhesive layer 51 is, for example, 3 g / m 2 Below, preferably 2.5g / m 2 Below, more preferably 2g / m 2 Below, more preferably 1.5 g / m 2 Below, particularly preferably 1g / m 2 Below, most preferably 0.5g / m 2 the following.
[0055] In one embodiment, in manufacturing the optical component 100, a laminate having a polarizer 30 and a first adhesive layer 51 is pre-formed. For example, the optical component 100 can be obtained by pre-stacking the polarizer 30 and the first adhesive layer 51 to form a laminate, adjusting the moisture content of the laminated portion of the polarizer 30 and the first adhesive layer 51, attaching the phase difference layer 40 to the laminate and setting the transparent plate 60. In addition, for example, the optical component 100 can be obtained by pre-stacking the polarizer 30, the first adhesive layer 51 and the phase difference layer 40 to form a laminate, adjusting the moisture content of the laminated portion of the polarizer 30 and the first adhesive layer 51, and setting the transparent plate 60 to the laminate. The above-mentioned adjustment of the water content can be achieved by placing the laminate in any suitable environment. For example, the moisture content is adjusted by placing the laminate in a heating environment above 90°C (heated to above 90°C). Furthermore, the moisture content is adjusted by, for example, placing the laminate in an environment with a temperature of 23° C. to 25° C. and a relative humidity of 52% to 55%.
[0056] <Polarizer>
[0057] The polarizer is typically a film containing a dichroic substance (typically, iodine).
[0058] The polarizer preferably exhibits absorption dichroism at any wavelength of 380nm to 780nm. The orthogonal transmittance (Tc) of the polarizer is preferably 0.5% or less, more preferably 0.1% or less, and further preferably 0.05% or less. The single transmittance (Ts) of the polarizer is, for example, 41.0% to 45.0%, and preferably 42.0% or more. The polarization degree (P) of the absorption-type polarizing film is, for example, 97.0% to 99.997%, preferably 99.0% or more, more preferably 99.5% or more, and further preferably 99.9% or more.
[0059] The thickness of the polarizer is not particularly limited, but is, for example, 1 μm or more and 50 μm or less. The thickness of the polarizer is preferably 40 μm or less, more preferably 30 μm or less, further preferably 20 μm or less, and may be 10 μm or less. By using a polarizer of such thickness, the above-mentioned moisture content can be well achieved. On the other hand, the thickness of the polarizer is preferably 2 μm or more, more preferably 3 μm or more.
[0060] The above-mentioned orthogonal transmittance, single transmittance and polarization degree can be measured, for example, using an ultraviolet visible spectrophotometer. The polarization degree P can be measured using an ultraviolet visible spectrophotometer to measure the single transmittance Ts, parallel transmittance Tp and orthogonal transmittance Tc, and the obtained Tp and Tc are obtained by the following formula. It should be noted that Ts, Tp and Tc are Y values obtained by measuring the 2-degree field of view (C light source) of JIS Z 8701 and correcting the visibility.
[0061] Polarization degree P (%) = {(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100
[0062] The polarizer can be produced by any appropriate method. Specifically, the polarizer can be produced using a single-layer resin film or a laminate of two or more layers.
[0063] The method for manufacturing polarizer by the resin film of the above-mentioned monolayer typically comprises dyeing and stretching the resin film using dichroic substances such as iodine or dichroic dyes. As the resin film, for example, hydrophilic polymer films such as polyvinyl alcohol (PVA) films, partially methylated PVA films, and partially saponified films of ethylene-vinyl acetate copolymers are used. The method may further comprise insolubilization treatment, swelling treatment, crosslinking treatment, etc. Such a manufacturing method is well known and commonly used in the art, so detailed description is omitted.
[0064] The polarizer obtained using the above-mentioned laminate can be made, for example, using a laminate of a resin substrate and a resin film or a resin layer (representatively a PVA-based resin layer). Specifically, it can be made in the following manner: a PVA-based resin solution is applied to a resin substrate and dried to form a PVA-based resin layer on the resin substrate, thereby obtaining a laminate of the resin substrate and the PVA-based resin layer; the laminate is stretched and dyed to make the PVA-based resin layer into a polarizer. In the present embodiment, it is preferred that a PVA-based resin layer comprising a halide and a PVA-based resin is formed on one side of the resin substrate. Stretching typically includes immersing the laminate in an aqueous boric acid solution for stretching. Furthermore, stretching may further include stretching the laminate in the air at a high temperature (for example, above 95°C) before stretching in an aqueous boric acid solution as required. In addition, in the present embodiment, it is preferred that the laminate is subjected to a drying shrinkage treatment in which the laminate shrinks by more than 2% in the width direction by heating while being conveyed in the length direction. Representatively, the manufacturing method of the present embodiment includes sequentially implementing an air auxiliary stretching treatment, a dyeing treatment, an underwater stretching treatment and a drying shrinkage treatment on the laminate. By introducing auxiliary stretching, even when PVA is coated on a thermoplastic resin, the crystallinity of PVA can be improved, and high optical properties can be achieved. In addition, by improving the orientation of PVA in advance, when immersed in water in the subsequent dyeing process and stretching process, the problems of reduction and dissolution of the orientation of PVA can be prevented, and high optical properties can be achieved. Furthermore, when the PVA-based resin layer is immersed in a liquid, the disorder of the orientation of the PVA molecules and the reduction of the orientation can be suppressed compared to the case where the PVA-based resin layer does not contain a halide, and high optical properties can be achieved. Furthermore, by utilizing a drying shrinkage treatment to shrink the laminate in the width direction, high optical properties can be achieved. A polarizer can be obtained by laminating a protective layer on the peeling surface after the resin substrate is peeled off from the obtained resin substrate / polarizer laminate, or on the surface opposite to the peeling surface. The details of the method for producing such a polarizer are described in, for example, Japanese Patent Application Laid-Open No. 2012-73580 and Japanese Patent No. 6470455. The entire contents of these publications are incorporated herein by reference.
[0065] The polarizer may contain boric acid. From the viewpoint of durability, the boric acid content of the polarizer is preferably 5% by weight or more, more preferably 10% by weight or more. When the boric acid content is less than 5% by weight, for example, the polarizer may be polyene-converted, and the durability may be reduced. On the other hand, the boric acid content of the polarizer is preferably 25% by weight or less. The boric acid content of the polarizer can be adjusted, for example, by adjusting the boric acid content in the aqueous solution used in the production process of the polarizer. The boric acid content can be calculated, for example, by the neutralization method using the following formula as the amount of boric acid contained in the polarizer per unit weight.
[0066] [Mathematical formula 1]
[0067]
[0068] The iodine content of the polarizer is preferably 2% by weight or more. If the iodine content of the polarizer is within such a range, for example, through a synergistic effect with the above-mentioned boric acid, curling that may occur during heating can be suppressed, and durability is excellent. On the other hand, the iodine content of the polarizer is preferably 10% by weight or less. It should be noted that the iodine content of the polarizer refers to the amount of all iodine contained in the polarizer. Specifically, in the polarizer, iodine can be iodide ions (I - ), iodine molecules (I2), polyiodide ions (I3 - 、I5 - ) etc., but refers to the amount of iodine including all these forms. The iodine content can be calculated, for example, by a standard curve method of fluorescent X-ray analysis.
[0069] The polyiodide ions are present in the polarizer as an iodine complex with PVA, for example. By forming such a complex, absorption dichroism can be exhibited in the wavelength range of visible light. Specifically, the complex of PVA and triiodide ion (PVA·I3 - ) has an absorption peak near 470nm, and the complex of PVA and pentaiodide ion (PVA·I5 - ) may have an absorption peak near 600 nm. As a result, polyiodide ions can absorb light in a wide range of visible light depending on their form. - ) may have an absorption peak near 230nm and does not substantially participate in the absorption of visible light. Therefore, the polyiodide ions present in the form of an iodine complex with PVA may mainly participate in the absorption performance of the polarizer.
[0070] <Protective layer>
[0071] The protective layer can be composed of any suitable film that can be used as a protective layer of a polarizer. As the material that becomes the main component of the film constituting the protective layer, for example, cellulose resins such as triacetyl cellulose (TAC), polyester resins, polyvinyl alcohol resins, polycarbonate resins, polyamide resins, polyimide resins, polyether sulfone resins, polysulfone resins, polystyrene resins, cycloolefin resins such as polynorbornene resins, polyolefin resins, (meth) acrylic resins, acetate resins, etc. can be cited. Among them, (meth) acrylic acid refers to acrylic acid and / or methacrylic acid.
[0072] The first protective layer may be subjected to surface treatments such as hard coating, anti-reflection, anti-adhesion, and anti-glare treatments as required. Specifically, the first protective layer may be formed of a laminated film having a surface treatment layer formed on the substrate using the film as a substrate. The thickness of the surface treatment layer is preferably 0.5 μm to 10 μm, more preferably 1 μm to 7 μm, and further preferably 2 μm to 5 μm.
[0073] The thickness of the first protective layer can be appropriately set. The thickness of the first protective layer is preferably 10 μm to 80 μm, more preferably 15 μm to 70 μm, and further preferably 20 μm to 50 μm. It should be noted that when the protective layer is surface treated, the thickness of the first protective layer is the thickness including the thickness of the surface treated layer.
[0074] The second protective layer is preferably optically isotropic. In this specification, "optically isotropic" means that the in-plane phase difference Re(550) is 0nm to 10nm, and the phase difference Rth(550) in the thickness direction is -10nm to +10nm. The thickness of the second protective layer is preferably 10μm to 80μm, more preferably 20μm to 70μm, and further preferably 30μm to 50μm.
[0075] In one embodiment, the moisture permeability of the first protective layer is preferably higher than that of the second protective layer. The moisture permeability can be determined, for example, by the cup method (JIS Z 0208). The moisture permeability can be measured, for example, under an environment of a temperature of 40° C. and a relative humidity of 92%.
[0076] <Adhesive Layer>
[0077] The form of the adhesive constituting the adhesive layer is not particularly limited, and for example, a water-based adhesive, a solvent-based adhesive, a hot melt adhesive, an active energy ray-curable adhesive, etc. are used. Among them, for example, a water-based adhesive or an active energy ray-curable adhesive is preferably used because the thickness of the adhesive layer can be reduced. The thickness of the adhesive layer is preferably 0.01 μm to 5 μm, and more preferably 0.03 μm to 3 μm.
[0078] <Phase difference layer>
[0079] The retardation layer may be a single layer as shown in the figure, or may have a laminated structure of two or more layers. When the retardation layer is a single layer, the retardation layer can function as a λ / 4 plate representatively. The retardation layer is provided representatively to impart an antireflection property to the organic EL display device. The refractive index characteristics of the retardation layer show a relationship of nx > ny = nz representatively. The in-plane retardation Re(550) of the retardation layer is preferably 100 nm to 190 nm, more preferably 110 nm to 170 nm, and further preferably 120 nm to 160 nm. It should be noted that "ny = nz" includes not only the case where ny and nz are exactly equal, but also the case where they are substantially equal. Specifically, it may sometimes be ny > nz or ny < nz. The Nz coefficient of the retardation layer is preferably 0.9 to 1.5, more preferably 0.9 to 1.3. By satisfying such a relationship, an organic EL display device having a very excellent reflected hue can be obtained.
[0080] When the retardation layer is a single layer, the retardation layer preferably shows an inverse dispersion wavelength characteristic in which the retardation value increases corresponding to the wavelength of the measurement light. In this case, Re(450) / Re(550) of the retardation layer is preferably 0.8 or more and less than 1, more preferably 0.8 or more and 0.95 or less. If it is such a configuration, very excellent antireflection characteristics can be achieved.
[0081] The angle formed by the slow axis of the retardation layer and the absorption axis of the polarizer is preferably 40° to 50°, more preferably 42° to 48°, and further preferably about 45°. If the angle is in such a range, by setting the retardation layer as a λ / 4 plate as described above, an organic EL display device having very excellent antireflection characteristics can be obtained.
[0082] As long as the retardation layer can satisfy the above-mentioned characteristics, it can be composed of any suitable material. Specifically, the retardation layer may be a resin film (including a stretched resin film), or an alignment cured layer of a liquid crystal compound. Preferably, the retardation layer is composed of a resin film. In this case, the thickness of the retardation layer is, for example, 10 μm to 100 μm, preferably 10 μm or more and 70 μm or less, and more preferably 20 μm or more and 60 μm or less.
[0083] As the resin contained in the above-mentioned resin film, polycarbonate resin, polyester carbonate resin, polyester resin, polyvinyl acetal resin, polyarylate resin, cyclic olefin resin, cellulose resin, polyvinyl alcohol resin, polyamide resin, polyimide resin, polyether resin, polystyrene resin, acrylic resin, etc. can be listed. These resins can be used alone or in combination. As a method of combination, for example, blending and copolymerization can be listed. In the case where the λ / 4 component shows an inverse dispersion wavelength characteristic, a resin film containing a polycarbonate resin or a polyester carbonate resin (hereinafter, sometimes referred to as a polycarbonate resin) can be appropriately used.
[0084] As the above-mentioned polycarbonate resin, any suitable polycarbonate resin can be used. For example, the polycarbonate resin contains structural units derived from fluorene dihydroxy compounds, structural units derived from isosorbide dihydroxy compounds, and structural units derived from at least one dihydroxy compound selected from the group consisting of alicyclic diols, alicyclic dimethanol, diethylene glycol, triethylene glycol or polyethylene glycol, and alkylene glycol or spiro glycol. Preferably, the polycarbonate resin contains structural units derived from fluorene dihydroxy compounds, structural units derived from isosorbide dihydroxy compounds, structural units derived from alicyclic dimethanol and / or structural units derived from diethylene glycol, triethylene glycol or polyethylene glycol; more preferably, it contains structural units derived from fluorene dihydroxy compounds, structural units derived from isosorbide dihydroxy compounds, and structural units derived from diethylene glycol, triethylene glycol or polyethylene glycol. The polycarbonate resin may also contain structural units derived from other dihydroxy compounds as needed. It should be noted that details of polycarbonate-based resins that can be suitably used for λ / 4 components and methods for forming λ / 4 components are described, for example, in Japanese Patent Publication No. 2014-10291, Japanese Patent Publication No. 2014-26266, Japanese Patent Publication No. 2015-212816, Japanese Patent Publication No. 2015-212817, and Japanese Patent Publication No. 2015-212818, and the descriptions in these publications are cited in this specification as reference.
[0085] <Adhesive Layer>
[0086] The thickness of the adhesive layer can be set to any appropriate thickness. For example, the thickness of the first adhesive layer 51 and the third adhesive layer 53 is preferably 1 μm to 30 μm, more preferably 3 μm to 20 μm. The thickness of the second adhesive layer 52 is, for example, 20 μm to 500 μm, more preferably 100 μm to 300 μm.
[0087] The adhesive layer can be made of any suitable adhesive. As a specific example, the adhesive layer can be made of an adhesive with polymers such as acrylic acid polymers, silicone polymers, polyesters, polyurethanes, polyamides, polyethers, fluorine-based or rubber-based polymers as base polymers. By adjusting the type, number, combination and proportion of the monomers constituting the base polymer of the adhesive, as well as the amount of cross-linking agent, reaction temperature, reaction time, etc., an adhesive with desired characteristics corresponding to the purpose can be prepared. The base polymer of the adhesive can be used alone or in combination of two or more. As the base polymer, an acrylic acid polymer is preferably used. Specifically, the adhesive layer is preferably made of an acrylic acid adhesive.
[0088] <Transparent plate>
[0089] As the transparent plate, a transparent plate having appropriate mechanical strength is used. As such a transparent plate, for example, a transparent resin plate such as an acrylic resin or a polycarbonate resin, or a glass plate is used. The thickness of the transparent plate is, for example, 0.5 mm to 5 mm.
[0090] [Organic EL panel]
[0091] The optical member described above can be used in an organic EL display device, and the organic EL display device according to an embodiment of the present invention includes the optical member described above. Figure 2 This is a schematic cross-sectional view schematically showing an organic EL panel according to an embodiment of the present invention. Specifically, this is a schematic cross-sectional view schematically showing an organic EL panel included in an organic EL display device according to an embodiment of the present invention.
[0092] The organic EL panel 200 includes an optical member 100 and an organic EL panel main body 70 . In the organic EL panel 200 , the optical member 100 is attached to the organic EL panel main body 70 via a third adhesive layer 53 .
[0093] The illustrated organic EL panel body 70 includes a substrate 71, and an upper structural layer 72 including a circuit layer including a thin film transistor (TFT), an organic light emitting diode (OLED), a sealing film for sealing the OLED, etc. For example, when a flexible substrate (e.g., a resin substrate) is used as the substrate 71, the obtained organic EL display device can be bent, flexed, folded, rolled up, etc. The upper structural layer 72 includes, for example, a nitrogen-containing layer (e.g., a nitride layer such as silicon nitride or silicon oxynitride), and ammonia (including ammonium ions) can be generated from the upper structural layer 72.
[0094] It is believed that if the polarizer 30 is exposed to a high temperature environment in a state where there is moisture in it, ammonia (substantially ammonium ions) is easily generated from the upper structural layer 72 of the organic EL panel body 70, and the ammonia that invades the polarizer 30 (polarizer 10) decomposes the dichroic substance (representatively, an iodine complex) contained in the polarizer 10 to cause discoloration and fading. It is also believed that if a transparent plate 60 is provided, moisture is easily sealed in the polarizer 30, and moisture becomes easy to flow into the side of the organic EL panel body 70, causing the generation of gases such as ammonia, which is easy to cause discoloration and fading of the polarizer 30 (polarizer 10). As described above, by adjusting the moisture content in the optical component 100, even if a transparent plate 60 is provided, the discoloration and fading of the polarizer 30 (polarizer 10) can be suppressed, and the durability is excellent. In addition, the problem of discoloration and fading of the polarizer can be solved without designing and changing the organic EL panel body 70.
[0095] Example
[0096] The present invention is specifically described below by way of examples, but the present invention is not limited to these examples. It should be noted that the thickness, phase difference value and moisture content are values measured by the following measuring methods. In addition, unless otherwise specified, "parts" and "%" are weight references.
[0097] <Thickness>
[0098] The thickness of 10 μm or less was measured using a scanning electron microscope (manufactured by JEOL Ltd., product name “JSM-7100F”). The thickness exceeding 10 μm was measured using a digital micrometer (manufactured by ANRITSU, product name “KC-351C”).
[0099] <Phase difference value>
[0100] The phase difference value at each wavelength at 23° C. was measured using a Mueller matrix polarimeter (manufactured by Axometrics, product name “Axoscan”).
[0101] <Water content>
[0102] After measuring the initial weight of a sample cut out of a size of 50 mm × 150 mm from the member (laminated body) to be measured, the sample was heated and dried at 105°C for 15 hours, and the weight immediately after drying was measured. Then, the weight immediately after drying was subtracted from the initial weight to calculate the moisture content per unit area (g / mm 2 ). It should be noted that the weight was measured under an environment of a temperature of 23° C. and a relative humidity of 55%.
[0103] [Example 1]
[0104] (Production of Polarizer)
[0105] A long roll of a polyvinyl alcohol (PVA) resin film (manufactured by Kuraray, "PE4500") with a thickness of 45 μm was uniaxially stretched in the length direction to 5.9 times the length in the length direction using a roll stretching machine, and then subjected to swelling treatment, dyeing treatment, cross-linking treatment and washing treatment in sequence, and then dried at 70°C for 5 minutes to produce a polarizer with a thickness of 18 μm.
[0106] In the above swelling treatment, the film was stretched to 2.2 times while being treated with pure water at 20°C. In the above dyeing treatment, the iodine concentration was adjusted so that the monomer transmittance of the obtained polarizer was 43.4%, and the film was stretched to 1.4 times while being treated in a 30°C aqueous solution having a weight ratio of iodine to potassium iodide of 1:7. The above crosslinking treatment was a two-stage crosslinking treatment. In the first stage of the crosslinking treatment, the film was stretched to 1.2 times while being treated in an aqueous solution obtained by dissolving boric acid and potassium iodide at 40°C. The boric acid content of the aqueous solution in the first stage of the crosslinking treatment was set to 5.0% by weight, and the potassium iodide content was set to 3.0% by weight. In the second stage of the crosslinking treatment, the film was stretched to 1.6 times while being treated in an aqueous solution obtained by dissolving boric acid and potassium iodide at 65°C. The boric acid content of the aqueous solution in the second stage of the crosslinking treatment was set to 4.3% by weight, and the potassium iodide content was set to 5.0% by weight. In the above washing treatment, the film was treated with a 20°C potassium iodide aqueous solution. The potassium iodide content of the aqueous solution for the washing treatment was set to 2.6% by weight.
[0107] (Production of polarizing film)
[0108] A 28 μm thick HC-TAC film is bonded to one side (first main surface) of the polarizer via an ultraviolet curing adhesive. Specifically, the adhesive is applied in such a manner that the thickness becomes 1.0 μm, and bonded using a rolling mill. Thereafter, the adhesive is cured by irradiating ultraviolet rays from the HC-TAC film side. It should be noted that the HC-TAC film is a film having a 3 μm thick hard coating (HC) layer formed on a 25 μm thick triacetylcellulose (TAC) film, and is bonded in such a manner that the TAC film becomes the polarizer side.
[0109] Next, an acrylic film having a lactone ring structure with a thickness of 20 μm was bonded to the other side (second main surface) of the polarizer via an ultraviolet curing adhesive. Specifically, the adhesive was applied so that the thickness was 1.0 μm, and bonded using a rolling mill. After that, ultraviolet rays were irradiated from the acrylic film side to cure the adhesive.
[0110] In this way, a polarizing plate is obtained.
[0111] (Preparation of acrylic adhesive composition)
[0112] A monomer mixture containing 99 parts by weight of butyl acrylate and 1 part by weight of 4-hydroxyethyl acrylate was added to a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube, and a cooler. Furthermore, 0.1 parts by weight of 2,2'-azobisisobutyronitrile as a polymerization initiator was added together with 100 parts by weight of ethyl acetate relative to 100 parts by weight of the monomer mixture, and nitrogen was introduced while slowly stirring to replace the inside of the flask with nitrogen. The liquid temperature in the flask was maintained at 55°C and a polymerization reaction was performed for 8 hours to prepare a solution of an acrylic polymer having a weight average molecular weight (Mw) of 1.8 million.
[0113] An acrylic adhesive composition was prepared by adding 0.02 parts by weight of an isocyanate crosslinking agent (trimethylolpropane / xylylene diisocyanate adduct, manufactured by Tosoh Corporation, “TAKENATE D110N”) and 0.2 parts by weight of a silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd., “X-41-1056”) to 100 parts by weight of the solid content of the obtained acrylic polymer solution.
[0114] (Preparation of the First Adhesive Layer)
[0115] The acrylic adhesive composition was applied onto a release liner (polyethylene terephthalate film treated with a silicone release agent, 38 μm thick, manufactured by Mitsubishi Chemical Polyester Film Co., Ltd., “MRF38”) so that the thickness of the adhesive layer after drying would be 20 μm, and dried at 90° C. for 1 minute to form a first adhesive layer on the release liner.
[0116] (Preparation of Polarizing Plate with Adhesive Layer)
[0117] The first adhesive layer was attached to the acrylic film side of the obtained polarizer, and the release liner was peeled off from the first adhesive layer. In this state, the polarizer with an adhesive layer was left for 24 hours at a temperature of 23° C. and a relative humidity of 55%. The moisture content of the obtained polarizer with an adhesive layer was 2.5 g / m 2 .
[0118] (Production of Phase Difference Film)
[0119] The polymerization was carried out using a batch polymerization apparatus comprising two vertical reactors equipped with stirring blades and a reflux cooler controlled at 100° C. 29.60 parts by mass (0.046 mol) of bis[9-(2-phenoxycarbonylethyl)fluoren-9-yl]methane, 29.21 parts by mass (0.200 mol) of isosorbide (ISB), 42.28 parts by mass (0.139 mol) of spiroglycol (SPG), 63.77 parts by mass (0.298 mol) of diphenyl carbonate (DPC) and 1.19×10 calcium acetate monohydrate as a catalyst were added. -2 Mass parts (6.78×10 -5 mol). After the reactor is replaced with nitrogen under reduced pressure, it is heated with a heat medium and stirring is started when the internal temperature reaches 100°C. After 40 minutes from the start of heating, the internal temperature reaches 220°C and is controlled to maintain this temperature. At the same time, the pressure is reduced and is set to 13.3 kPa in 90 minutes after reaching 220°C. The phenol vapor produced as a by-product with the polymerization reaction is introduced into a 100°C reflux cooler, and some monomer components contained in the phenol vapor are returned to the reactor. The uncondensed phenol vapor is introduced into a 45°C condenser for recovery. After nitrogen is introduced into the first reactor and the pressure is temporarily restored to atmospheric pressure, the oligomerized reaction liquid in the first reactor is transferred to the second reactor. Next, the temperature and pressure reduction in the second reactor are started, and the internal temperature is set to 240°C and the pressure is set to 0.2 kPa in 50 minutes. After that, the polymerization is carried out until the specified stirring power is reached. When a predetermined power was reached, nitrogen was introduced into the reactor to restore the pressure, and the produced polyester carbonate resin was extruded into water, and the strands were cut to obtain pellets.
[0120] The obtained polyester carbonate resin (pellets) was vacuum dried at 80°C for 5 hours, and then a film-making device equipped with a single screw extruder (manufactured by Toshiba Machine Co., Ltd., roller setting temperature: 250°C), a T-die (width 200mm, setting temperature: 250°C), a chilled roll (setting temperature: 120-130°C) and a winder was used to prepare a long strip of resin film with a thickness of 135 μm. The obtained long strip of resin film was stretched in the width direction at a stretching temperature of 143°C and a stretching ratio of 2.8 times to obtain a retardation film with a thickness of 48 μm. The obtained retardation film has a Re(550) of 143 nm, a Re(450) / Re(550) of 0.86, and an Nz coefficient of 1.12.
[0121] (Fabrication of optical components)
[0122] The retardation film is bonded to the first pressure-sensitive adhesive layer side of the pressure-sensitive adhesive layer-attached polarizing plate.
[0123] As a transparent plate, a slide glass (manufactured by Matsunami Glass Industries, product name "S200423") was prepared, and the prepared transparent plate was bonded to the polarizer side of the polarizer with an adhesive layer via an adhesive having a thickness of 250 μm.
[0124] In this way, an optical component is manufactured.
[0125] [Example 2]
[0126] In the preparation of the polarizing plate with an adhesive layer, the polarizing plate with an adhesive layer was placed in a heating environment at a temperature of 90° C. for 2 hours to set the moisture content of the polarizing plate with an adhesive layer to 0.2 g / m 2 , except for this, the same operation as in Example 1 was carried out to produce an optical component.
[0127] [Comparative Example 1]
[0128] In the preparation of the polarizing plate with an adhesive layer, the polarizing plate with an adhesive layer was placed in an environment of a temperature of 40° C. and a relative humidity of 92% for 5 hours to set the moisture content of the polarizing plate with an adhesive layer to 6.7 g / m 2 , except for this, the same operation as in Example 1 was carried out to produce an optical component.
[0129] The following evaluations were performed on the Examples and Comparative Examples. The evaluation results are summarized in Table 1.
[0130] <Evaluation>
[0131] The obtained optical member (size: 50 mm×150 mm) was bonded to a non-alkali glass plate having a 500 nm thick silicon oxynitride film formed on its surface via a pressure-sensitive adhesive layer formed as described below, and then heated at 95° C. for 75 hours as required for vehicle-mounted displays and the like.
[0132] The cross transmittance Tc of the optical member before and after heating was measured using an ultraviolet visible spectrophotometer ("LPF-2000" manufactured by Otsuka Electronics Co., Ltd.), and the cross transmittance change ΔTc (ΔTc=Tc after heating-Tc before heating) was calculated.
[0133] In addition, the reflectivity of the optical member before and after heating was measured using a spectrophotometer ("CM-2600d" manufactured by Konica Minolta). The measurement was performed with a reflector ("Cerapeel DMS-X42" manufactured by TORAY ADVANCED FILM) superimposed on the back side of the glass, and the reflectivity change (reflectivity after heating - reflectivity before heating) was calculated.
[0134] It should be noted that the measurement position of the orthogonal transmittance Tc and the reflectance was set to the central part of the optical member.
[0135] (Formation of Adhesive Layer)
[0136] A monomer mixture containing 94.9 parts by weight of butyl acrylate, 5 parts by weight of acrylic acid and 0.1 parts by weight of 2-hydroxyethyl acrylate was added to a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet pipe and a cooler. Furthermore, 0.3 parts by weight of dibenzoyl peroxide as a polymerization initiator was added together with ethyl acetate to 100 parts by weight of the monomer mixture, and nitrogen was introduced while slowly stirring to replace the flask with nitrogen. The liquid temperature in the flask was maintained at 60° C. and a polymerization reaction was performed for 7 hours. Then, ethyl acetate was added to the obtained reaction solution to adjust the solid content concentration to 30% by weight, and a solution of an acrylic polymer having a weight average molecular weight (Mw) of 2.2 million was prepared.
[0137] An acrylic adhesive was prepared by mixing 0.6 parts by weight of trimethylolpropane / tolylene diisocyanate adduct (trade name: CORONATE L, manufactured by Tosoh Corporation) and 0.075 parts by weight of a silane coupling agent (trade name: KBM403, manufactured by Shin-Etsu Chemical Co., Ltd.) with respect to 100 parts by weight of the solid content of the obtained acrylic polymer solution.
[0138] The obtained acrylic pressure-sensitive adhesive was applied onto the release liner so that the pressure-sensitive adhesive layer had a thickness of 20 μm after drying, and dried at 90° C. for 1 minute to form a pressure-sensitive adhesive layer on the release liner.
[0139] Table 1
[0140] Example 1 Example 2 Comparative Example 1 <![CDATA[Water content (g / m 2 )]]> 2.5 0.2 6.7 ΔTc(%) 0.17 0.0004 43 Reflectivity change (%) 0.35 0.13 41
[0141] Figure 3A This is a photograph obtained by observing the optical member before heating of Comparative Example 1 in the above evaluation from above. Figure 3B This is a photograph obtained by observing the heated optical component of Comparative Example 1 in the above evaluation from above. Figure 3A and Figure 3B As shown in , the optical member of Comparative Example 1 changes color (changes to red) by heating.
[0142] The present invention is not limited to the above-described embodiments, and various modifications are possible. For example, the configuration shown in the above-described embodiments may be replaced with a configuration that is substantially the same as the configuration shown in the above-described embodiments, a configuration that exhibits the same function and effect, or a configuration that can achieve the same purpose.
[0143] Industrial Applicability
[0144] The optical member according to the embodiment of the present invention can be suitably used in, for example, an organic EL panel and an organic EL display device.
Claims
1. An optical component comprising: A polarizing plate comprising a polarizer having a first principal surface and a second principal surface facing each other, and a first protective layer disposed on the first principal surface side of the polarizer; a transparent plate disposed on the first principal surface side of the polarizer; A phase difference layer, which is arranged on the second main surface side of the polarizer; and a first adhesive layer, the first adhesive layer being arranged between the polarizing plate and the phase difference layer and being arranged adjacent to the polarizing plate; The moisture content of the laminated portion of the polarizing plate and the first adhesive layer is 3 g / m 2 the following. 2 . An organic EL panel comprising the optical member according to claim 1 and an organic EL panel body.
3. A method for manufacturing an optical component, comprising: A laminated body is prepared, the laminated body comprising a polarizing plate and a first adhesive layer, the polarizing plate comprising a polarizer having a first principal surface and a second principal surface facing each other and a first protective layer arranged on the first principal surface side of the polarizer, the first adhesive layer being arranged on the second principal surface side of the polarizer and adjacent to the polarizing plate, the moisture content of the laminated portion of the polarizing plate and the first adhesive layer being 3 g / m 2 the following; Disposing a transparent plate on the polarizing plate side of the stack; and A phase difference layer is bonded onto the first pressure-sensitive adhesive layer of the laminate.
4. A method for manufacturing an optical component, comprising: A laminate is prepared, the laminate comprising a polarizing plate, a first adhesive layer disposed adjacent to the polarizing plate, and a phase difference layer disposed on the second principal surface side of the polarizer in this order, the polarizing plate comprising a polarizer having a first principal surface and a second principal surface facing each other, and a first protective layer disposed on the first principal surface side of the polarizer, the moisture content of the laminated portion of the polarizing plate and the first adhesive layer being 3 g / m 2 the following; A transparent plate is provided on the polarizing plate side of the laminate.
Citation Information
Patent Citations
Optically active liquid crystal compound having cyano group
JP1989070455A
Composite optical retardation plate, circularly polarizing plate and liquid crystal display, organic el display device
JP2002372622A
Manufacturing method of thin polarizing film
JP2012073580A
Circularly polarizing plate and display device
JP2014010291A
Polarizing plate and organic el panel
JP2014026266A